2003
DOI: 10.2298/jmmb0302201s
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of platinum metals and alloys from chloride melts

Abstract: The structure of platinum metals and their alloys deposited by the electrolysis of chloride melts have been investigated. The cathodic deposits were both in the form of compact layers and dendrites. All the alloys of platinum metals obtained are solid solutions in the whole range of composition. Depending on the experimental conditions the layers had columnar, stratum and spiral (dissipative) structures. The stratum and dissipative structures were observed in the case of alloys only

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 1 publication
0
5
0
3
Order By: Relevance
“…Being applied in jewelry design, fragrant and fibrous ebony is often encased with gems. A wide range of techniques in material surface finishing is applied in modern jewelry design [5,6,10]. The reticulated sample of 800 silver is illustrated in Figure 1.…”
Section: The Effect Of Forms and Surface Characteristics On The Qualimentioning
confidence: 99%
“…Being applied in jewelry design, fragrant and fibrous ebony is often encased with gems. A wide range of techniques in material surface finishing is applied in modern jewelry design [5,6,10]. The reticulated sample of 800 silver is illustrated in Figure 1.…”
Section: The Effect Of Forms and Surface Characteristics On The Qualimentioning
confidence: 99%
“…Several routes were used to extract metal from some metallic oxide such as carbo-thermic reduction 26 , electrolysis from molten salt for some active metals 27 and carbo-chlorination. As it was thermodynamically favorable for the formation of chlorides, Ilic et al 28 discussed the chlorination of nickel oxides and nickel ferrites with or without additives and found that the chlorination degree of Ni, Fe, Cr increased with the increase in the quantity of coal.…”
Section: Procedures Of the Carbo-chlorination Of Sio2mentioning
confidence: 99%
“…Much attention has been focused on the effects of various preparation parameters on the morphology and microstructure of Ir coating and determined some properties of Ir coating, including density, purity, hardness and oxidation resistance [23][24][25][26][27]. Growth mechanism of laminar Ir coatings and effects of high temperature heat treatment on the mechanical properties is very crucial to its applications.…”
Section: Introductionmentioning
confidence: 99%